Seasonal coordination of leaf hydraulics and gas exchange in a wintergreen fern - Prats, Kyra A (AoB Plants, 2020)
Wintergreen fern Polystichum acrostichoides has fronds that are photosynthetically active year-round, despite diurnal and seasonal changes in soil moisture, air temperature and light availability. This species can fix much of its annual carbon during periods when the deciduous canopy is open. Yet, remaining photosynthetically active year-round requires the maintenance of photosynthetic and hydraulic systems that are vulnerable to freeze–thaw cycles. We aimed to determine the anatomical and physiological strategies P. acrostichoides uses to maintain positive carbon gain, and the coordination between the hydraulic and photosynthetic systems. We found that the first night below 0 °C led to 25 % loss of conductivity (PLC) in stipes, suggesting that winter-induced embolism occurred. Maximum photosynthetic rate and chlorophyll fluorescence declined during winter but recovered by spring, despite PLC remaining high; the remaining hydraulic capacity was sufficient to supply the leaves with water. The onset of colder temperatures coincided with the development of a necrotic hinge zone at the stipe base, allowing fronds to overwinter lying prostrate and maintain a favourable leaf temperature. Our conductivity data show that the hinge zone did not affect leaf hydraulics because of the flexibility of the vasculature. Collectively, these strategies help P. acrostichoides to survive in northeastern forests.